Sita: The Justly Emancipated Woman in Chitra Banerji Divakaruni’s The Forest of Enchantments - Rathore, Geetanjali (International Journal of Scientific Research and Management (IJSRM), 2021)
Sita has always been described as a docile and meek woman sine ages. The Indian English writers of the twenty first century has totally changed the age old narrative and brought out in the society the valiant and courageous Sita. Some writers focus her as awarrior, others as a very courageous woman who has no time to indulge in self pity. Chitra Banerjee Divakaruni also focuses on the courageous and most witty side of her Sita. she shows her wit in the management of the household. How sita deftly keeps the male ego under control and makes her emancipated is the focus of the present paper. Male ego and suppression are alos the focus of this paper.